Pengaruh Pengetahuan Wajib Pajak Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Membayar Pajak Kendaraan Bermotor Masyarakat Di Cikarang Barat - Suripto Moh Zulkifli; Adi Suprayoga; Rinaldi Sri Herlambang (BADAN PENERBIT STIEPARI PRESS, 2023)
Payment of vehicle tax is one of the main sources of local revenue. To improve compliance in paying taxes, sufficient knowledge of vehicle tax information and taxpayer awareness initiatives is required. The purpose of this study was to determine the effect of taxpayer knowledge and taxpayer awareness on compliance with paying motor vehicle taxes. This research was conducted in West Cikarang. The number of samples in this study were 100 respondents with the sampling method using the convenience sampling method. Data was collected using a questionnaire method and processed using SPSS version 25 software. The data analysis technique used in this research was multiple linear regression. Based on the results of the analysis, it can be seen that the knowledge of taxpayers and awareness of taxpayers has an effect on compliance with paying motor vehicle taxes.